Nutritional Rickets Among Children: A Retrospective Study from Saudi Arabia - Darraj H; Hakami KM; Maghrabi R; Bakri N; Alhazmi MH; Names AA; Akkur A; Sayegh M; Alhazmi A; Khubrani SM; Gohal G; Alomar AH; et al. (Dove Medical Press, 2023)
Hussam Darraj,1 Khalid M Hakami,1 Rawan Maghrabi,1 Nawaf Bakri,1 Mohammed H Alhazmi,1 Abdellh A Names,1 Ahmed Akkur,1 Maram Sayegh,1 Asma Alhazmi,1 Saad M Khubrani,1 Gassem Gohal,1 Amro H Alomar,2 Abdulaziz H Alhazmi1 1Faculty of Medicine, Jazan University, Jazan, 45142, Saudi Arabia; 2King Fahad Central Hospital, Ministry of Health, Jazan, 85534, Saudi ArabiaCorrespondence: Abdulaziz H Alhazmi, Email Abalhazmi@jazanu.edu.saBackground: Nutritional rickets remains a significant concern in certain countries, with increasing prevalence attributed to factors such as limited sunlight exposure and undernourishment. This study aimed to identify the factors associated with rickets due to nutritional deficiency in children from Jazan Province, southwestern Saudi Arabia.Methods: A retrospective cross-sectional study was conducted using descriptive data from medical records at a tertiary hospital in Jazan Province. Records of patients diagnosed with rickets between January 2010 and December 2020 were analyzed. Symptomatic rickets cases from pediatric clinics were included, and diagnoses were based on biochemical and clinical tests. Risk factors were assessed using patient medical records. Data were analyzed using percentages, mean, and standard deviation.Results: The study included 84 patients with rickets (53 females and 31 males), primarily between 11- 18 years old. The mean body mass index (BMI) of the participants was 21.21. The most common risk factor was nutritional deficiencies, including vitamin D deficiency or calcium deficiency, with 75 patients reporting a family history of vitamin D deficiency. The children had limited sunlight exposure and low levels of calcium and vitamin D. Malnutrition was identified as the highest risk factor for rickets in the study population.Conclusion: Nutritional rickets appears to be prevalent in the Jazan Province, emphasizing the need for government organizations to address this preventable disease. Adequate sun exposure and recommended dietary vitamin D intake are crucial to prevent rickets, as this study detected inadequate levels of calcium and vitamin D in children. National studies are required to further identify risk factors and develop appropriate strategies.Keywords: nutritional rickets, vitamin D, breastfeeding, Saudi Arabia